Implementation of Quizwhizzer as A Teaching Evaluation Media Based on Educational Games in Informatics Subjects at Al-Maliki Islamic Boarding School - Wati, Indah Rahma; Taufik , Taufik; Hakim, Arif Rahman (FKIP - Universitas Riau, 2025)
The rapid development of digital technology in education requires innovative approaches to teaching and evaluation that not only measure outcomes but also motivate students to learn actively. Informatics, as a subject in junior high schools, is often perceived as difficult by students, which makes effective and engaging evaluation methods essential. This study aims to implement and analyze the effectiveness of QuizWhizzer as an educational game-based evaluation medium in Informatics learning at SMP Pondok Pesantren Al-Maliki. The research employed an experimental method with a Pretest–Posttest Control Group Design, involving 38 students divided equally into an experimental class using QuizWhizzer and a control class applying conventional evaluation. Data were collected through pretests, posttests, questionnaires, and expert validation. The results show that QuizWhizzer was validated as feasible by material experts and received positive responses from students, who considered it fun and motivating. Furthermore, the experimental class showed higher improvement in learning outcomes compared to the control class. In conclusion, QuizWhizzer effectively enhances students’ engagement, motivation, and academic performance, making it a promising alternative for modern digital-based evaluation in education.